CECT IN THE ADRENOCORTICAL CARCINOMAS: RECOGNIZING THE TYPICAL MORPHOLOGICAL FEATURES - KRITIKAL; SHARMA, RAJARAM; LODHA, SAMBHAV; THAKKAR, HEMANGINI; BADHE, PADMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This study was characterization of adrenal masses on computer tomography (CT) using shape, size, and enhancement patterns. Methods: It is a retrospective study of 86 adrenal masses with morphological differences in the appearance and enhancement patterns (histopathologically proven 36 pheochromocytoma [PCCs], 26 adrenal cortical carcinoma [ACCs], one lymphoma, 22 metastases, and one schwannoma). Two experienced radiologists who were unaware of the histopathological diagnosis reviewed the computed tomography scans, morphological parameters had been noted, along with attenuations measured in Hounsfield units for all the phases of contrast-enhanced computed tomography. Results: Necrosis had been seen in all the cases of ACCs with a loss of adeniform shape. ACCs were significantly less enhancing in arterial phase and venous phase than PCC; however, no significant difference was seen with lymphomas, metastasis, and schwannoma. 25/33 (75.5%) ACC showed heterogeneous enhancement (due to the presence of necrosis) in the VP. Conclusion: Heterogenous architecture with a size of more than 5 cm is relatively specific for diagnosing ACC. No specific enhancement pattern could well differentiate ACC from lymphoma, metastases, and schwannoma.